Desimal Berulang untuk suatu Numerator - Affaf, Moh. (APOTEMA : Jurnal Program Studi Pendidikan Matematika, 2018)
Let ð denote a positive integer relatively prime to 10 and ð be natural number less than ð and relatively prime to ð. Let the period of ððbe ððwith ð > 1. Break the repeating block of ðð digits up into ð sub blocks, each of length ð, and let ðµ(ðð, ð, ð) denote the sum of these ð blocks. In 1836 has been proved and re-proofed in 2013 that if ð is a prime greater than 5, and the period of 1ðis 2ð, then ðµ(ð1, ð, 2) = 10ð â 1. In 2004, has been showed that if ð is a prime greater than 5, and the period of 1ðis 3ð, then ðµ(ð1, ð, 3) = 10ð â 1. In 2005, also was showed that if ð is a prime greater than 5, and the period of 1ðis ðð, then ðµ(ð1, ð, 3) is multiply of 10ð â 1. In 2007, study of repeating decimal of 1ðis expanded, that ð dont have to prime greater than 5, but just relatively prime to 10. In this paper, will be investigated property of repeating decimal of ððwith ð dont have to equal to 1, but enough less than ðand relatively prime to ð.